Revisiting Quality Failure Costs in Construction - Love, Peter; Teo, Pauline; Morrison, J. (American Society of Civil Engineers, 2018)
© 2017 American Society of Civil Engineers. Quality failure costs have been reported to range from less than 1 to over 20% of a project's original contract's value (OCV). Inconsistencies in their definition and determination have rendered such costs often being cited inappropriately to support a case for addressing poor quality in construction. Quality failure costs, which are expressed in the form of nonconformances (NCRs) costs, are derived and analyzed for 218 projects delivered by a contractor between 2006 and 2015. A total of 7,082 NCRs are categorized and quantified in accordance to their cost, and the differences among project type, procurement, and contract size are statistically examined. The analysis revealed that (1) mean NCR costs were 0.18% of OCV; (2) structural steel and concrete subcontracted works had the highest levels of NCRs; and (3) differences were found in the cost of NCRs among different procurement methods and contract sizes. The research provides the international construction community with invaluable insight into the real costs of quality failure that have been borne by a contractor. Thus, the paper makes a call to reinvigorate the need to engage with performance benchmarking so as to engender process improvement throughout the international construction industry.